Balance Screening of Vestibular Function in Subjects Aged 4 Years and Older: A Living Laboratory Experience - Bermúdez Rey, María Carolina; Clark, Torin K.; Merfeld, Daniel M. (Frontiers in Neurology, 2017)
To better understand the various individual factors that contribute to balance and the relation to fall risk, we performed the modified Romberg Test of Standing Balance on Firm and Compliant Support, with 1,174 participants between 4 and 83 years of age. This research was conducted in the Living Laboratory® at the Museum of Science, Boston. We specifically focus on balance test condition 4, in which individuals stand on memory foam with eyes closed, and must rely on their vestibular system; therefore, performance in this balance test condition provides a proxy for vestibular function. We look for balance variations associated with sex, race/ethnicity, health factors and age. We found that balance test performance is stable between 10-39 year of age, with a slight increase in the failure rate for participants 4-9 years of age, suggesting a period of balance development in younger children. For participants 40 years and older, the balance test failure rate increases progressively with age. Diabetes and obesity are the two main health factors we found associated with poor balance, with test condition 4 failure rates of 57% and 19%, respectively. An increase in the odds of having fallen in the last year was associated with a decrease in the time to failure; once individuals dropped below a time failure of 10 seconds, there was a significant 5.5-fold increase in the odds of having fallen in the last 12 months. These data alert us to screen for poor vestibular function in individuals 40 years and older or suffering from diabetes, in order to undertake the necessary diagnostic and rehabilitation measures, with a focus on reducing the morbidity and mortality of falls.